STRUCTURAL ANALYSIS OF THE BREAKWATER AT MAILEPPET BEACH, SOUTH SIBERUT DISTRICT, MENTAWAI ISLANDS REGENCY - Nazili Nazili; Robby Hotter; Innosensius Richoik Tatabburuk (Journal of Scientech Research and Development, 2026)
Maileppet Beach in the South Siberut District, Mentawai Islands Regency, is experiencing significant erosion due to ocean waves and tides from the Indian Ocean. The erosion has threatened roads, settlements, and public facilities in the coastal area. This study aims to analyze wave characteristics and design the dimensions of a sloping side breakwater structure as a coastal protection measure. The data used includes wind, wave, and tidal data over five years from BMKG Teluk Bayur, Padang. The analysis was conducted using the SPM (1984) method, wave transformation, wave breaking, Run-Up, and stability of protective layers using Hudson's formula. The analysis results show a significant wave height of 0.45 meters with a period of 2.7 seconds, a breaking wave height of 1.29 meters, and a run-up of 1.03 meters. The sloping side breakwater structure is planned using tetrapods with a main protective layer weight of 9 tons and a construction width of 15 meters.